RESOLUSI KONFLIK AKIBAT PERNIKAHAN DIBAWAH UMUR: (PERSPEKTIF HUKUM ISLAM) - karisnazen, Risma Istiqomah; Agis Yulisertiasih; Widodo Hami (Al-Qawaid Research Centre of the Department of Islamic Family Law, 2023)
This research discusses conflict resolution that arises as a result of underage marriage, with a focus on the perspective of Islamic law. Child marriage often involves complex issues such as individual rights, child welfare, and religious norms. This aims to provide a deeper understanding of how to resolve conflicts that arise as a result of underage marriage based on the principles of Islamic law. This research uses a qualitative library research method, which is based on analysis of literature and relevant text sources. The aim is to provide insight and a better understanding of how Islamic law treats the issue of underage marriage, including the minimum age rules, conditions and necessary consent. Thus, this research seeks to provide a better framework and solution in dealing with conflicts related to underage marriage by considering the principles of Islamic law. Based on the research results, it will provide a clearer view of how Islamic law can provide a framework and solution in dealing with conflicts related to underage marriage. This research provides important insight into how to resolve conflicts resulting from underage marriage to serve as a guide for society and the authorities in implementing the principles of Islamic law in the context of underage marriage. Keywords : marriage, conflict, underage, Islamic law.